Laboratory exercises in developmental biology - Cruz, Yolanda P. (Academic Press, 1993)
This intensive manual provides students with valuable information and insights into animal development at the organismal, cellular, and subcellular levels. The book uses both descriptive and investigative approaches that emphasize techniques, key experiments, and data analysis. Key Features: Provides a broad introductory view of developmental systems. Teaches both classical embryology and modern experimental approaches. Contains seventeen laboratory exercises, written in step-by-step style. Organized with additional notes to students and preparators. Lists questions and references for each exercise. Special chapters give introductions to the scientific process, use of the microscope, and the writing of scientific papers. Illustrated with detailed line drawings.